An autonomous drone-based system for inspection of electrical substations. (21st April 2021) - Langåker, Helge-André; Kjerkreit, Håkon; Syversen, Christoffer L; Moore, Richard JD; Holhjem, Øystein H; Jensen, Irene; Morrison, Aiden; Transeth, Aksel A; Kvien, Oddgeir; Berg, Gunnar; Olsen, Thomas A; Hatlestad, Alexander; et al.
In the years to come, large power grid operators will operate and maintain an ever-increasing asset base. New innovative solutions are needed to increase the quality and efficiency of asset management to avoid corresponding growth in resources and cost. To this end, autonomous unmanned aerial vehicles (UAVs) provide a range of possibilities. Here, we present a novel prototype solution for autonomous and remotely operated inspection missions with resident drones on electrical substations, comprising: (1) an autonomous drone with sense and avoid and robustness to harsh weather capability; (2) a drone hangar for remote operations; and (3) drone operations and data acquisition management software. Further, we discuss the possibilities and challenges that such a system offers and give an overview of requirements that are key to realizing the potential of drones for improved asset management. These requirements are based on years of operational experience with electrical substations combined with the lessons learned during the development and testing of our drone system. We also experimentally investigate safety distances between the drone and high-voltage infrastructure. We demonstrate the usefulness of our autonomous inspection solution through extensive field testing at one of Statnett's fully operational electrical substations.